Control of the speed in real time of a dc motor controlled by fuzzy logic type pd + i using labview - Rodríguez Bustinza, Ricardo (2011)
In this article, a method is presented based on artificial intelligence to control a plant DC motor for a personal microcomputer (PC), that interacted hardware and software achieves the control of the speed of the DC motor in real time using the control algorithm Fuzzy-PD+I. The acquisition of data and identification of the parameters of the DC motor have been necessary for the control of the speed of the motor DC, by means of the card of acquisition of data PCI NIDAQ 6024E whose interface runs in the real time that the Workshop Real-Time uses (RTW), the file of data is processed with the tool of identification of the program called IDENT of Matlab. The prototype of the system computer-controller is designed using the graphic programming of LabVIEW, in this case use of the tools Fuzzy Logic Control and Simulation Module. The control in real time of the system is carried out in the laboratory using the digital-to-analogical converter (DAC) and incremental encoder formed by two sensors of effect hall that is possible to process the signs from the analogical input of the NIDAQ by means of a convertor frequency voltage. The results of computer simulation are verified experimentally, those that demonstrate that the designed control sign can make that the exit of the system prototype follows the references imposed with minimum overshoot and null steady-state error.